Intravenous thrombolysis for acute ischaemic stroke in the elderly: data from the Baden‐Wuerttemberg stroke registry. (23rd October 2015) - Reuter, B.; Gumbinger, C.; Sauer, T.; Wiethölter, H.; Bruder, I.; Rode, S.; Ringleb, P. A.; Kern, R.; Hacke, W.; Hennerici, M. G.; ,
Abstract : Background and purpose: In Europe intravenous thrombolysis (IVT) for ischaemic stroke is still not approved for patients aged >80 years. However, elderly patients are frequently treated based on individual decision making. In a retrospective observational study a consecutive and prospective stroke registry in southwest Germany was analysed. Methods: The data registry collected 101 349 patients with ischaemic stroke hospitalized from January 2008 to December 2012. Of these, 38 575 (38%) were aged 80 years and older and 10 286 (10.1%) underwent IVT. Favourable outcome at discharge was defined as modified Rankin Scale (mRS) ≤1 or not worse than prior to stroke. Multiple logistic regression models stratified by 10‐year age groups were used to assess the relationship between IVT and mRS at discharge, adjusted for patient characteristics, admitting facility and length of hospital stay. Results: The highest IVT rate was 15% in patients aged <50 years, with a continuous decline down to 8% in patients aged ≥90 years. Adjusted odds ratios and 95% confidence intervals for patients 80–89 years of age were 2.20 (1.95–2.47) ( P < 0.0001) and 1.25 (0.88–1.78) ( P = 0.21) for patients >90 years of age, compared to patients of the same age decade not treated with IVT. Conclusions: The evidence from routine hospital care in southwest Germany indicates that IVT is an effective treatment also for aged patients with ischaemic stroke in an age range between 80 and 89 years. Although no clear evidence for the effectiveness of IVT beyond 90 years was found, treatment should also be carefully considered in these patients. High age should not discourage from treatment. Abstract : Clickhere for the corresponding questions to this CME article.